Evaluation of Work Motivation and Work Efficiency on the Success of Telemarketing Staff in Achieving IndiHome Sales Targets at PT. Telkom Access Takengon Branch - Riski, Rezi; Fadhilla, Hanifa Nur (Universitas Muhammadiyah Pontianak, 2026)
This study explores how work motivation and efficiency influence the performance of telemarketing staff in achieving IndiHome sales targets at PT. Telkom Access Takengon Branch. Using a qualitative approach with interviews, observation, and documentation, findings reveal that high motivation enhances enthusiasm, consistency, and creativity in customer engagement. Efficiency improves the bidding process, data management, and sales conversions. Although targets were not fully met, the synergy between motivation and efficiency led to better outcomes. Future research should broaden the scope and consider additional variables such as job satisfaction, organizational culture, and leadership style to provide deeper insights.